THINKING ANALYSIS AND PROBLEM SOLVING - Yuni Agustina; Neviyarni (Yayasan Citra Dharma Cindekia, 2021)
This article uses references from related literature studies to discuss the analysis of thinking and problem solving, where the concept of thinking and problem solving is a higher or highest level of cognitive behavior, namely thinking. The ability to think is only possible if you already have some concepts with strong reasoning skills. The essence of thinking and problem solving includes general forms of problem solving, the stages of problem solving, namely understanding and explaining (explaining) the problem, proposing various options, determining solutions and implementing options, and checking whether the problem is successful. This article is designed to explain some problems, especially the nature of thinking and problem solving, general forms of problem-solving tasks, stages of problem solving, theories of thinking and problem solving, Piaget's theory of cognitive development, and some practical suggestions. As an introduction to education thinking about drawing conclusions, and problem solving is a way for people to reach conclusions about a particular problem or problem. In other words, problem solving is a situation that requires a person to find solutions to various problems.